Impact of single structural voids on fatigue properties of AISI 316L manufactured by laser powder bed fusion. (July 2021) - Kotzem, Daniel; Kleszczynski, Stefan; Stern, Felix; Elspaß, Arno; Tenkamp, Jochen; Witt, Gerd; Walther, Frank
Highlights: Defined structural defects were implemented in PBF-LB/M manufactured 316L specimens. Individual internal defects (edge length ≥ 1, 000 µm) lead to a significant reduction in UTS. Material shows high defect tolerance against small internal defects during cyclic loading. Applicability of the √area-parameter model for defects ≥ 1000 µm was evaluated. Abstract: The laser powder bed fusion of metals (PBF-LB/M) process is already exploited in several industrial applications. The process itself allows to introduce artificial defects which can later be characterized by their influence on the resulting mechanical properties. In this study, the influence of isolated single structural defects (0.3 mm ≤ √area ≤ 1.5 mm) on the fatigue properties is discussed and the √area-parameter model is applied. The obtained results show that the investigated material is highly defect tolerant as artificial defects with √area = 0.3 mm are not crack initiating. Specimens with a defect of √area = 1.0–1.5 mm clearly show crack initiation and propagation starting from the defect, and a fatigue strength estimation tends to be more conservative.